Study on obesity and Influence of dietary factors on the weight status of an adult population in Jamnagar city of Gujarat: A cross-sectional analytical study - Vadera Bhavin; Yadav Sudha; Yadav Babusingh; Parmar Dipesh; Unadkat Sumit (Wolters Kluwer Medknow Publications, 2010)
Background: Obesity has reached epidemic proportions globally and is a major contributor to the global burden of chronic diseases. Dietary factors are the major modifiable factors through which many of the external forces promoting weight gain act. Objectives: The objectives were to find the prevalence of overweight and obesity in the urban population of Jamnagar and to explore the effect of dietary factors on the weight status of the people. Materials and Methods: A cross-sectional study was conducted among the adult population of Jamnagar city. Cluster sampling technique was used to select study samples. Data were collected in a prestructured questionnaire by interviewing subjects through house-to-house visits. Data were analyzed in Epi Info and appropriate statistical methods were used. Results: The prevalence of overweight and obesity was found to be 22.04% and 5.20%, respectively. Overweight was more prevalent in females than males. The prevalence rose with an increase in age up to 60 years. Among dietary factors, the total calorie intake and habit of snacking had a positive association with weight gain (P < 0.05). The mean intake of oil was more and the mean intake of vegetables was less among overweight subjects than nonoverweight subjects (P < 0.05). Conclusion: The prevalence of overweight and obesity in the urban population in Jamnagar was found to be 22.04% and 5.20%, respectively. Total calorie intake as well as composition of diet was the important dietary factor affecting weight gain.